Survey for the Role of Continuing Education Center Programs in Developing the Skills of Human Resources Working in the Libraries of Basra University - Sharif Qassem, Marwa; Abdel Rahman Abdel Wahed , Prof.Dr. Amal (Basra studies journal, 2022)
The research aims at introducing continuing education center programs and activities that provided by the Center for Development and Continuing Education to university libraries, as well as the desired benefit from participating in its courses and activities. The questionnaire tool in collecting data and information based on human resources working in university libraries and centers libraries, which numbered (145) individuals, and ratios were used in the research. Research reached out many results, including: 1-There are a large number of human resources who participate in continuing education courses and programs and provide library services to beneficiaries. 2-The desire of many human resources to participate in continuing education activities and programs due to the requirements of office work and increasing their skills and competencies. The research came out with a number of recommendations, including: 1- The need for encouragement from the authorities responsible for continuing education programs to stimulate human resources and their participation in these courses. 2-Providing the means and means for the success of continuing education programs and activities.